Animal welfare in experimental orthopedic surgery of dogs: an analysis of the Brazilian view - Sugauara,Rosângela Rumi (2018)
ABSTRACT: The aim of this paper was to conduct a bibliometry search about Brazilian scientific publications that describe experimental orthopedic surgeries in dogs. It was analyzed 14 publications, and there was wide variation in the number of experimental animals, showing that there is no consensus on the appropriate number for science experiment with dogs. Most articles had been reviewed by an ethics committee (13/14, 92.85%) and only two articles (2/14; 14.28%) did not report the use of analgesic protocol. Among analgesics, morphine was the most widely used, noted in seven studies (7/14; 42.85%). In six of the articles (6/14; 42.85%), the final destination of animals was not informed, but in four experiments (4/14; 28.57%) the dogs were euthanized. In four studies (4/14; 28.57%) the animals were sent for adoption. In conclusion, the ethics in animal research in Brazil has advanced, but is necessary proper planning in sample size.